2019
DOI: 10.1111/jace.16694
|View full text |Cite
|
Sign up to set email alerts
|

Effects of crystal structure and cation size on molten silicate reactivity with environmental barrier coating materials

Abstract: Rare earth (RE) disilicates are utilized in environmental barrier coatings to protect Si‐based engine components from destructive reactions with water vapor and other combustion species. These coating materials, however, degrade when exposed to molten silicate deposits in the engine. Four RE‐disilicates (RE2Si2O7, RE = Er, Dy, Gd, Nd) are analyzed herein in thermochemical interactions with glassy calcium‐magnesium‐aluminosilicate (CMAS) compositions at 1400°C. Crystalline reaction products included RE2Si2O7, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 45 publications
0
31
0
2
Order By: Relevance
“…This is driving the formation of Y-Ca-Si apatite [15,20,34,37]. Most recently, Stokes et al [38] have confirmed that the propensity of RE-Ca-Si apatite formation decreases with the increasing difference between RE 3+ and Ca 2+ radii in RE 2 Si 2 O 7 powders that have interacted with different CMASs (at 1400°C for 1 h), where RE = Nd (1.163 Å), Gd (1.107 Å), Dy (1.083 Å), or Er (1.062 Å), in that order. Also, these RE 2 Si 2 O 7 have been shown to have lower enthalpies for apatite formation compared to Yb 2 Si 2 O 7 , where Yb 3+ has the smallest ionic radius [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is driving the formation of Y-Ca-Si apatite [15,20,34,37]. Most recently, Stokes et al [38] have confirmed that the propensity of RE-Ca-Si apatite formation decreases with the increasing difference between RE 3+ and Ca 2+ radii in RE 2 Si 2 O 7 powders that have interacted with different CMASs (at 1400°C for 1 h), where RE = Nd (1.163 Å), Gd (1.107 Å), Dy (1.083 Å), or Er (1.062 Å), in that order. Also, these RE 2 Si 2 O 7 have been shown to have lower enthalpies for apatite formation compared to Yb 2 Si 2 O 7 , where Yb 3+ has the smallest ionic radius [39].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the Ca/Si ratio in the remaining CMAS is still less than 0.44, that is, in the NASA CMAS, resulting in virtually no apatite formation and the suppression of "blister" cracks in all the pellets. In this context, one of CMASs Stokes et al [38] used has a Ca/Si ratio (0.096) similar to that of the IVA CMAS. They found that the interaction between that CMAS and RE 2 Si 2 O 7 (RE = Er, Dy, Gd, or Nd) powders resulted in little or no apatite formation, but crystallization of α-SiO 2 (cristobalite) instead.…”
Section: Discussionmentioning
confidence: 99%
“…Premature failure of the coating upon cooling can result due to this internal stress development [11,12]. Additionally, molten CMAS has been shown to thermochemically interact with numerous EBC candidate materials based on rare-earth (RE) silicates, causing dissolution-precipitation of new and often undesirable phases [13,14,15]. Each of these deleterious CMAS interactions may lead to weakened or compromised coatings and ultimately failure of the overall CMC component.…”
Section: Introductionmentioning
confidence: 99%
“…Most rely on modifying the composition of the coating material to either favor reactions that consume the deposit melt and block pathways for melt infiltration into porous TBCs, 18,19 or to minimize the reactivity between dense, impenetrable EBCs and surface deposits. [20][21][22] In both cases, calcium rare earth oxyapatite [nominally Ca 2 RE 8 (SiO 4 ) 6 O 2 ] has been identified as an important reaction product that exists in equilibrium with a broad range of CMFAS deposit compositions. Tailored porosity, non-wetting surface structures or materials, and non-reactive, impermeable metallic layers also provide benefits, as long as those structures are stable in the operating environment.…”
Section: Introductionmentioning
confidence: 99%